Deradicalization through Double-Loop Learning? How the Egyptian Gamaa Islamiya Renounced Violence. (3rd August 2022) - Goerzig, Carolin
Abstract: The transformation of the Gamaa Islamiya can be understood by analyzing it against Argyris and Schön's double-loop learning model. This paper bases the analysis on five books published by the Gamaa Islamiya, which include comprehensive elaborations on internal reflections and criticism of Al-Qaeda. While the Gamaa Islamiya's learning can be framed with the model of double-loop learning, Al-Qaeda's reactions can be depicted as a less evolved single-loop learning system. This case is relevant for the discovery of key mechanisms of de-radicalization that could be used as a blueprint for other groups.